2011
DOI: 10.5194/acp-11-1989-2011
|View full text |Cite
|
Sign up to set email alerts
|

Importance of secondary sources in the atmospheric budgets of formic and acetic acids

Abstract: We present a detailed budget of formic and acetic acids, two of the most abundant trace gases in the atmosphere. Our bottom-up estimate of the global source of formic and acetic acids are ~1200 and ~1400 Gmol yr<sup>−1</sup>, dominated by photochemical oxidation of biogenic volatile organic compounds, in particular isoprene. Their sinks are dominated by wet and dry deposition. We use the GEOS-Chem chemical transport model to evaluate this budget against an extensive suite of measurements from groun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
412
7

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 301 publications
(446 citation statements)
references
References 162 publications
(203 reference statements)
27
412
7
Order By: Relevance
“…Concerning HCOOH, several studies have highlighted the underestimation of emissions in the models by a factor of nine in the marine boundary layer (Baboukas et al, 2000) and an order of magnitude for the free troposphere (Von Kuhlmann et al, 2003). Recently, Paulot et al (2011) investigated an underestimation in the model by a factor of two to five compared to polar FTIR measurements at Thule (Greenland; 76 • N, 69 • W), confirming the missing local sources in the HCOOH budget simulated in the model. Finally, HCOOH and H 2 CO spectroscopic parameters have been refined recently (HITRAN 2008, http: //www.cfa.harvard.edu/hitran/updates.html, Rothman et al, 2009.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Concerning HCOOH, several studies have highlighted the underestimation of emissions in the models by a factor of nine in the marine boundary layer (Baboukas et al, 2000) and an order of magnitude for the free troposphere (Von Kuhlmann et al, 2003). Recently, Paulot et al (2011) investigated an underestimation in the model by a factor of two to five compared to polar FTIR measurements at Thule (Greenland; 76 • N, 69 • W), confirming the missing local sources in the HCOOH budget simulated in the model. Finally, HCOOH and H 2 CO spectroscopic parameters have been refined recently (HITRAN 2008, http: //www.cfa.harvard.edu/hitran/updates.html, Rothman et al, 2009.…”
Section: Introductionmentioning
confidence: 77%
“…HCOOH is removed through oxidation by OH as well as by dry and wet depositions . However, a recent study suggested a missing source in the HCOOH budget of the northern latitudes and inferred its lifetime to be about three to four days (Paulot et al, 2011).…”
Section: Seasonal Variabilities Of Hcn Ch 3 Oh Hcooh and H 2 Comentioning
confidence: 99%
See 3 more Smart Citations